Effects of vertical confinement on the flow of polymer solutions in planar constriction microchannels - Raihan, Mahmud Kamal; Wu, Sen; Dort, Heston; Baghdady, Micah; Song, Yongxin; Xuan, Xiangchun (Soft matter, 2022)
The flow of polymer solutions under extensional conditions is frequently encountered in numerous engineering fields. Planar contraction and/or expansion microchannels have been a subject of interest for many studies in that regard, which, however, have mostly focused on shallow channel structures. We investigate here the effect of changing the depth of contraction-expansion microchannels on the flow responses of three types of polymer solutions and water. The flow of viscoelastic polyethylene oxide (PEO) solution is found to become more stable with suppressed vortex formation and growth in the contraction part while being less stable in the expansion part with the increase of the channel depth. These opposing trends in the contraction and expansion flows are noted to have similarities with our recent findings of constriction length-dependent instabilities in the same PEO solution (M. K. Raihan, S. Wu, Y. Song and X. Xuan, Soft Matter, 2021, 17 , 9198-9209), where the contraction flow gets stabilized while the expansion flow becomes destabilized with the increase of the constriction length. In contrast, the entire flow becomes less stable in deeper channels for the shear-thinning xanthan gum (XG) solution as well as the shear thinning and viscoelastic polyacrylamide (PAA) solution. This observation aligns with that of water flow, which is attributed to the reduced top/bottom wall stabilizing effects. The contraction flow of viscoelastic polyethylene oxide (PEO) solution gets stabilized with suppressed vortex formation and growth in the deeper contraction-expansion microchannels.